The haloes and environments of nearby galaxies (HERON): I. Imaging, sample characteristics, and envelope diameters - Rich, R. Michael; Koch-Hansen, Andreas (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We use a dedicated 0.7-m telescope to image the haloes of 119 galaxies in the Local Volume to μr ∼ 28-30 mag arcsec−2. The sample is primarily from t